2012
DOI: 10.4252/wjsc.v4.i10.101
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells as treatment of adjuvant rheumatoid arthritis in a rat model

Abstract: MSC enhance the efficacy of CFA-induced arthritis treatment, most likely through the modulation of the expression of cytokines and amelioration of pathological changes in joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Therefore, MSCs may modulate the immune response and induce anti-inflammatory effects [34,35,36]. Furthermore, the availability of MSCs for autologous and allogeneic transplantation makes them useful in the treatment of SCI.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MSCs may modulate the immune response and induce anti-inflammatory effects [34,35,36]. Furthermore, the availability of MSCs for autologous and allogeneic transplantation makes them useful in the treatment of SCI.…”
Section: Resultsmentioning
confidence: 99%
“…91,92 Besides BM, MSCs can be isolated from adipose tissues, lung, gingiva, placenta, liver, cord blood, and umbilical cord. [93][94][95][96] There are some similar experiments showing that MSCs from the other tissues also can polarize macrophages to the alternatively activated M2 phenotype. In parallel observation with human placental MSCs, Abumaree et al 97 also found that the human placental MSCs also have potent anti-inflammatory and immunosuppressive actions via converting macrophages from a proinflammatory M1 phenotype to an anti-inflammatory M2 phenotype.…”
mentioning
confidence: 77%
“…Lymphocytes and monocytes generally secrete this cytokine; however, other PBMCs can synthesize and release IL-10 [32] . Recent in vivo studies have observed an increased level of IL-10 after transplanting MSCs or injecting the cell-free medium of these cells to animal models [33][34][35] . Although cell-cell interactions between MSCs and different cells of the immune system play a significant role in immune-modulation, the secretion of soluble factors is more important to suppress the immune system [6] .…”
Section: Discussionmentioning
confidence: 99%